2007 19th International Conference on Applied Electromagnetics and Communications 2007
DOI: 10.1109/icecom.2007.4544451
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of uniaxial multilayer cylinders used for invisible cloak realization

Abstract: Recently, an uniaxial multilayer cylinder cloak which does not scatter electromagnetic wave was proposed. However, the metamaterial realization only reduces the scattered field and is suitable only for excitation by a TM-polarized wave. Furthermore, it works only in a narrow frequency band. The purpose of this paper is to analyze such a cloak and to characterize the achieved "invisibility" in mathematical terms by calculating the scattered field and equivalent blockage width -the structure width that is actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…A very recent analytical study [4] revealed that the anisotropic cloak introduced in [3] has an operating bandwidth of only 0.24%. Thus, it appears that the material dispersion is indeed a major limiting factor on the operating bandwidth of the proposed cloaking devices.…”
Section: Dispersion Of 'Plasma-like' Metamaterials and Its Influence Omentioning
confidence: 99%
“…A very recent analytical study [4] revealed that the anisotropic cloak introduced in [3] has an operating bandwidth of only 0.24%. Thus, it appears that the material dispersion is indeed a major limiting factor on the operating bandwidth of the proposed cloaking devices.…”
Section: Dispersion Of 'Plasma-like' Metamaterials and Its Influence Omentioning
confidence: 99%
“…In Cloak I, only μ ρ , μ j and ε z components are relevant for the normal incidence of TM z polarisation. Second validation of the presented relation is provided by comparing the result of normalised bi-static scattering width of DB and PEC cylinder coated with Cloak I in TM z excitation [13]. This result can prove the validity of the presented formulations.…”
Section: Numerical Results and Validationmentioning
confidence: 85%
“…Also, the total scattering width of the D′B′ boundary condition is given in Fig. 2b compared with the results that were calculated by Ivsic et al [13] for TE z excitation. This comparison shows an excellent agreement and validates the presented relations and results.…”
Section: Numerical Results and Validationmentioning
confidence: 95%
See 1 more Smart Citation
“…Scattering coefficient study in different cylindrical wave orders have been shown with simplified material properties [11,12]. Until now, discussions on the bandwidth and practical limitations of electromagnetic cloak present in the published results [13][14][15][16][17][18] are few in number.…”
Section: Introductionmentioning
confidence: 96%